The cross border supply of services and the need to harmonise the VAT rules that apply - Brown, Christopher (Department of Finance and Tax, 2016)
Services cannot be subject to border controls in the same way as goods, which makes the charging and collection of VAT in these instances more complex. In many jurisdictions, VAT is collected on the cross-border supply of services via the reverse charge mechanism. This mechanism transfers the liability for the payment of VAT to the local recipient of the service (ie the customer), which creates a situation where foreign suppliers are not required to register in these jurisdictions and accordingly decreases the cost of compliance - a key contributor to the principle of VAT neutrality. In most cases, where the local recipient is liable for the payment of reverse charge VAT in respect of an imported service, a corresponding input tax credit is available where the service is on-supplied, resulting in a VAT neutral position for the local recipient. The problem arises where the reverse charge mechanism is applied inconsistently from country to country - where in some instances the VAT accounted for on imported services cannot be claimed as a credit due on the supply. In such instances, the reverse charge VAT represents an actual cost to the recipient of the service, which will then invariably be on-charged to the final consumer. In such cases, VAT will be levied on VAT and the final consumer will be subject to double VAT taxation. The Organisation for Economic Co-operation and Development (OECD) released the International VAT/GST Guidelines in April 2014 which has the "aim of reducing the uncertainty and risks of double taxation and unintended non-taxation that result from inconsistencies in the application of VAT in a cross-border context." These guidelines are not aimed at providing detailed prescriptions for national legislation but rather seek to identify objectives and suggest means for achieving them. These Guidelines are an important step in initiating a more harmonised approach to VAT. While not binding, they represent the key principles of a successful VAT structure that should be inherent in all VAT legislation. This paper is an analysis of the feasibility of implementing a harmonised approach to VAT in Africa, with particular regard to the application of the reverse charge mechanism, and the different means by which the incidence of double VAT taxation that results, can be prevented. This position is compared to that of the European Community (EC) in order to highlight the need for consistency in the application of VAT legislation of different African jurisdictions. The varying application of the reverse charge mechanism in African countries is one such example of how uncoordinated unilateral measures can result, and have the potential, not only to increase the cost of compliance and doing business in Africa, but also to create barriers and discourage, particularly, cross-border trade in services. By initiating a more harmonised approached to VAT legislation across Africa, the inconsistencies in the application of similar principles can be avoided, facilitating trade and easing the compliance burden on vendors.